Electrical explosion of metals in fast-rising megagauss magnetic fields; Physics of Plasmas; Vol. 15, iss. 4 - Chaikovsky S. A.; Oreshkin V. I. Vladimir Ivanovich; Mesyats G. A. Gennady Andreyevich; Ratakhin N. A. Nikolay Aleksandrovich (2009, 2009)
Title screen